OVERVIEW OF KNOWLEDGE ABOUT ANEMIA PREVENTION WITH BLOOD SUPLEMENT TABLETS AT SMAS DHARMA PANCASILA MEDAN - Utari, Anggita; Zahara, Mila; Sintia, Ayunda; Sibuea, Alya Az Zahra (Pena Cendekia Insani, 2025)
The purpose of this research is to find out the picture of knowledge about the prevention of anemia with blood suplement tablets. The sampling technique in this study was carried out with a simple random sampling technique in which 32 students of class XI MIA were selected at SMAS Dharma Pancasila Medan. The method of this research is an experiment with a one group pretest-posttest research design. Data analysis was performed using descriptive analysis and N-Gain test analysis. The results of this study show that there is an influence and improvement in the understanding of the material seen from the increase in pretest and posttest scores. After being analyzed with the N-Gain test, students' knowledge is in the moderate range because each child must have different reasoning abilities. Meanwhile, based on the interpretation of the effectiveness of the counseling process, it shows that the interpretation is less effective. This is likely due to the lack of extension media displayed in the process of delivering material.